Facilitating the development of emergency nursing in Africa: Operational challenges and successes - Petra Brysiewicz; Tricia Scott; Emmanuel Acheampong; Ivy Muya (African Journal of Emergency Medicine, 2021)
The World Health Assembly declared 2020 as the ‘Year of the Nurse and the Midwife’ in recognition of the critical contribution of both professions to global health. Nurses globally are having to do more with less and in the already resource deficient African context, significant adaptation and leadership is required in the way emergency nurses work if they are to be effective in reducing mortality and morbidity within emergency populations. In 2011, an emergency nursing group, representing the largest group of nurses in Africa, swiftly engaged with this process by publishing the document ‘Developing a framework for emergency nursing practice in Africa’ (2012). From this document a strategic plan was devised within a tight timeframe, to operationalise the quest for enhanced emergency nursing in Africa. The purpose of this paper is to describe this development of emergency nursing in Africa and to explain the operational challenges and successes, as well as the lessons learnt in order to assist with future planning.